Web Design in a Nutshell / A Desktop Quick Reference - Robbins Niederst Jennifer (O'Reilly, 2006)
A thorough, yet concise reference on everything you need to know to create web pages. Completely reviewed for standards compliance, including CSS 2.1 and XHTML 1.0. Foreword, Preface, The Web Environment, Web Standards, Accessibility, Internationalization, The Structural Layer: XML and (X)HTML, HTML and XHTML Overview, Text Elements, Images and Objects, Tables, Frames, Forms, The Presentation Layer: Cascading Style Sheets, Selectors, Color and Backgrounds, Floating and Positioning, CSS for Tables, CSS Techniques, The Behavioral Layer: JavaScript and the ROM, DOM Scripting, Web Graphics, GIF Format, JPEG Format, PNG Format, Animated GIFs, Media, Audio on the Web, Video on the WEB, The Flash Platform, Printing from the Web, Appendixes, Glossary, Index.